Type 2 diabetes progression differently affects endothelial function and vascular contractility in the aorta and the pulmonary artery - Melo, Bernardete F. (2021)
Funding: B.F.M. is supported by PhD Grant from Portuguese Foundation for Science and Technology Reference PD/BD/128336/2017. FOM and JFS are supported by Portuguese Foundation for Science and Technology contracts CEECIND/04266/2017 and CEECIND/02428/2018